2007
DOI: 10.1089/fpd.2007.0013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vaccination to ReduceSalmonellaPrevalence in Live and Slaughtered Swine: A Systematic Review of Literature from 1979 to 2007

Abstract: A systematic review was conducted to evaluate the efficacy of vaccination to reduce Salmonella prevalence in market weight finisher swine. A search of online databases and selected conference proceedings was conducted to identify relevant studies. The review process followed relevance screening, methodological quality assessment, and data extraction. Although multiple outcomes were frequently reported, only outcomes describing culture of Salmonella were extracted. Five clinical trials and 23 challenge studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…These trials lacked information related to the method of treatment allocation, the grouping of animals relative to treatment allocation, the use or non-use of blinding and the method of statistical analysis (Elbers and Schukken, 1995). Further, several systematic reviews in pre-harvest food safety (Denagamage et al, 2007;O'Connor et al, 2008) and animal health (O'Connor et al, 2006;Wellman and O'Connor, 2007;Burns and O'Connor, 2008) have noted a lack of reporting of group allocation methods; blinding and details related to intervention protocols, outcome assessments and statistical analysis methods in some published clinical trials. This lack of consistency in reporting makes it almost impossible to summarize sufficient data appropriately, thereby affecting the ability to arrive at an overall conclusion on a particular intervention or outcome.…”
Section: Incomplete and Inaccurate Reporting In Published Livestock Imentioning
confidence: 99%
“…These trials lacked information related to the method of treatment allocation, the grouping of animals relative to treatment allocation, the use or non-use of blinding and the method of statistical analysis (Elbers and Schukken, 1995). Further, several systematic reviews in pre-harvest food safety (Denagamage et al, 2007;O'Connor et al, 2008) and animal health (O'Connor et al, 2006;Wellman and O'Connor, 2007;Burns and O'Connor, 2008) have noted a lack of reporting of group allocation methods; blinding and details related to intervention protocols, outcome assessments and statistical analysis methods in some published clinical trials. This lack of consistency in reporting makes it almost impossible to summarize sufficient data appropriately, thereby affecting the ability to arrive at an overall conclusion on a particular intervention or outcome.…”
Section: Incomplete and Inaccurate Reporting In Published Livestock Imentioning
confidence: 99%
“…To model imperfect vaccines, animals are classified based on both their epidemiological and vaccination status (e.g., susceptible and susceptible vaccines) and the vaccine effects are explicitly included in the model. Several studies indicate that available Salmonella vaccines are imperfect (Zhang-Barber et al, 1999;House et al, 2001;Denagamage et al, 2007;Heider et al, 2008). For example, some vaccines decrease susceptibility to infection, whereas others shorten the infectious period or reduce fecal shedding.…”
Section: Vaccinationmentioning
confidence: 99%
“…In most studies the use of Salmonella Typhimurium vaccines significantly decreased clinical signs and excretion of Salmonella (Springer et al, 2001;Roesler et al, 2004Roesler et al, , 2006Eddicks et al, 2009;Farzan and Friendship, 2010;Hotes et al, 2011;Hur et al, 2011). However, Denagamage et al (2007) concluded in their review that the design and reporting deficiencies in many studies (e.g. little detail on population type, sample size, type of vaccine, dose and dosing regimens) meant that the association between vaccination and Salmonella reduction in finisher swine was promising, but not proven.…”
Section: Introductionmentioning
confidence: 99%